Maternal BMI and pregnancy outcomes: An analytical basis for health promotion strategies - Eko Mindarsih; Dewi Setyaningsih; Heny Noor Wijayanti; Suwarsi; Santi Susanti (Alma Ata University Press, 2026)
Background: The nutritional status of pregnant women, as assessed by Body Mass Index (BMI), plays a crucial role in influencing the process and outcomes of childbirth. BMI is used as an indicator of maternal nutritional status, categorized as underweight (<18.5), normal (18.5–24.9), and overweight (≥25). BMI has been shown to be associated with various maternal complications. Although BMI demonstrates a significant impact on maternal outcomes, further research is needed to serve as a basis for health promotion strategies in antenatal care services. Objective: This study aims to analyze the relationship between maternal BMI and pregnancy outcomes, and to establish an analytical basis for health promotion strategies. Methods: This study used an observational analytical design with a cross-sectional approach and was conducted in the working area of Ngemplak I Health Center, Sleman, Special Region of Yogyakarta. The research sample was 98 pregnant women who met the inclusion criteria, selected using a purposive sampling technique. Data were collected through questionnaires sourced from the KIA book, then analyzed using the Chi-Square test with a significance level of p <0.05. Results: The study showed a significant relationship between maternal BMI and type of delivery (p = 0.037), while no significant associations were found with hemorrhage (p = 0.620), premature labor (p = 0.820), and prolonged labor (p = 0.825). Conclusion: There is a significant relationship between maternal nutritional status based on BMI and the type of delivery. However, no significant relationship was observed with hemorrhage, premature labor, or prolonged labor. These findings can serve as a basis for health promotion strategies, particularly in nutritional education during pregnancy to prevent delivery complications